ADAPT AND OVERCOME: REVISING US NAVAL DOCTRINE AND POLICY IN AN ERA OF UNCONVENTIONAL CONFLICT - Lowther, Adam B. (Scientia Militaria - South African Journal of Military Studies, 2011)
When the Quadrennial Defense Review (QDR) was released in February of 2006, the United States was in the middle of a multi-front Global War on Terror (GWOT) that had been underway for more than four years. Beginning with the initial response to the 9/11 attacks in October of 2001, the US Navy began to play a significant part in the unconventional operations that characterised the early days of OPERATION ENDURING FREEDOM. While the Navy carried out its mission admirably supporting Special Operations Forces (SOF) by providing the USS Kitty Hawk (CV 63) as a “lily pad”, which enabled Rangers, Delta operators, Green Berets, and SEALs to move in and out of Afghanistan from a maritime staging area, it was a role well outside the norm of American naval operations and one the Navy is yet to fully embrace.